Plant regeneration through somatic embryogenesis in cell suspensions of Cenchrus ciliaris L. - Shipra Goyal; Vijaya Chatterjee; Vishvas M. Kulkarni; Vishnu Bhat (Plant Methods, 2023)
Abstract Background This study aims to establish cell suspension culture, its maintenance and induction of somatic embryogenesis, and in vitro plant regeneration in Cenchrus ciliaris L. Suspension cultures are relatively homogenous cell lines facilitating uniform access to nutrition. These are ideal sources of competent cells for genetic transformation. Results Callus was initiated by culturing immature inflorescences of Cenchrus ciliaris cv. IGFRI-3108 on Murashige and Skoog (MS) medium containing 3 mg l−1 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.5 mg l−1 6-benzylaminopurine (BAP) with 30 g l−1 sucrose. Cell suspension cultures were established in liquid MS medium using an inoculum size of 10 g l−1. These were maintained to achieve embryogenic cell/regeneration competent cultures. Growth curve analysis and a subculture interval of 20 days were determined to harvest cells at the end of the exponential phase. The cell doubling time was found to be 11 days. Somatic embryogenesis was accomplished in MS medium containing 1 mg l−1 2,4-D, 1 mg l−1 BAP along with growth adjuvants, 300 mg l−1 casein hydrolysate, 400 mg l−1 glutamine and 300 mg l−1 proline. The highest number (16 ± 3.78/per inoculum) of shoots regenerated on this medium. The elongation and rooting of shoots were recorded on basal MS and ½ MS media, respectively. Rooted plants were successfully transferred to pots containing a Soilrite and cocopeat mixture in a 3:1 proportion for 3–4 weeks and later successfully acclimatized in the greenhouse with a 60% survival rate. The genetic fidelity of 12 regenerated plants was analysed using RAPD primers that were genetically identical to the mother plant. Conclusion Cell suspension culture-based in vitro plant regeneration of C. ciliaris involved the establishment, maintenance and progression of somatic embryogenesis during shoot and root development. The inherent limitation of callus-mediated in vitro plant regeneration reducing the regeneration potential due to the aging of the calli has been overcome.